Fast and efficient analysis of transient nonlinear heat conduction problems using combined approximations (CA) method. (June 2016) - Feng, S.Z.; Cui, X.Y.; Li, A.M.
Highlights: CA method is used for efficient transient nonlinear heat transfer analysis. Accurate results are obtained using a small number of basic vectors. The CA method can achieve high level of efficiency. Abstract: The combined approximations (CA) method is very efficient and can provide high quality results, when dealing with structural optimization problems. In this study, the CA method is utilized to reduce the computational effort in transient nonlinear heat transfer analysis. In the CA approach, binomial series are used as high quality basis vectors for reduced basis expression. Transient nonlinear temperature fields are then calculated without solving complete set of nonlinear system equations. Both two-dimensional and three-dimensional numerical problems are studied to verify the accuracy and efficiency of CA method, when solving transient nonlinear heat conduction problems.